2009
DOI: 10.1007/s11916-009-0077-y
|View full text |Cite
|
Sign up to set email alerts
|

Chronic tension-type headache

Abstract: Tension-type headache is the most common headache type worldwide. Chronic tension-type headache (CTTH) affects 2% to 3% of patients, yet it represents the least talked about subtype of chronic daily headache. There is much debate in the headache community on whether CTTH exists as its own entity or is a milder form of chronic migraine (CM), because there are similarities and differences between the two headache forms. This article reviews CTTH, as well as the current pathophysiology and treatment, and discusse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
2
0
1
Order By: Relevance
“…Muscular factors play a role not only in the acute episode of TTH. On the basis of numerous pain perception, imaging, pharmacological and longitudinal studies, it has been demonstrated that prolonged nociceptive input from peripheral myofascial tissues in subjects with episodic TTH can lead to sensitization of the central nervous system and in this way to transformation from episodic to chronic TTH (Bendtsen, ; Bendtsen and Jensen, ; Fernandez‐de‐Las‐Penas et al., ; Ailani, ; Chen, ; Cathcart et al., ; Bendtsen and Fernandez‐de‐la‐Penas, ; Bezov et al., ) (Fig. ).…”
Section: Muscular Factorsmentioning
confidence: 99%
“…Muscular factors play a role not only in the acute episode of TTH. On the basis of numerous pain perception, imaging, pharmacological and longitudinal studies, it has been demonstrated that prolonged nociceptive input from peripheral myofascial tissues in subjects with episodic TTH can lead to sensitization of the central nervous system and in this way to transformation from episodic to chronic TTH (Bendtsen, ; Bendtsen and Jensen, ; Fernandez‐de‐Las‐Penas et al., ; Ailani, ; Chen, ; Cathcart et al., ; Bendtsen and Fernandez‐de‐la‐Penas, ; Bezov et al., ) (Fig. ).…”
Section: Muscular Factorsmentioning
confidence: 99%
“…Die vorliegende Studie ist eine Post-hoc-Analyse der Langzeitstudie der ACHIEVE-I- und -II-Studien. In dieser Verlängerungsstudie wurden die Sicherheit und Wirksamkeit von Ubrogepant 50 mg und 100 mg im Vergleich zur Routinebehandlung über 52 Wochen untersucht 4 . In diese Analyse wurden Teilnehmerinnen einbezogen, die mindestens eine perimenstruelle oder nicht perimenstruelle Migräneattacke mit Ubrogepant 50 mg oder 100 mg behandelt hatten.…”
Section: Ubrogepant Zur Akuttherapie Der Migräne: äHnliche Wirksamkei...unclassified
“…From other forms of primary headaches such as migraine, cluster headache and hemicrania continua it is most often told by differential diagnostics of the clinical picture. It is to be told by differential diagnostics from secondary headaches that appear due to high intracranial pressure, caused either by tumour processes, normotensive hydrocephalus and like [1,[16][17][18][19].…”
mentioning
confidence: 99%